Juvenile polyposis syndrome: A case report - Edwin Mogere; Elijah Mwaura; Mark Waithaka; Victor Mutua; Maurice Mugao; Chris vonCsefalvay; Dennis Mukamati (Clinical Case Reports, 2023)
Abstract Juvenile polyposis syndrome (JPS) is an autosomal dominant disease that is characterized by multiple hamartomatous polyps. Patients with JPS are at increased risk for developing colorectal and gastric cancer. JPS was diagnosed by endoscopy and histology, and the patient underwent surgery, total proctocolectomy and ileal pouch–anal anastomosis.